International Council for Standardization in Haematology (ICSH) recommendations for processing of blood samples for coagulation testing. (27th September 2021) - Kitchen, Steve; Adcock, Dorothy M.; Dauer, Ray; Kristoffersen, Ann‐Helen; Lippi, Giuseppe; Mackie, Ian; Marlar, Richard A.; Nair, Sukesh
Abstract: This guidance document has been prepared on behalf of the International Council for Standardization in Haematology (ICSH). The aim of the document is to provide guidance and recommendations for the processing of citrated blood samples for coagulation tests in clinical laboratories in all regions of the world. The following areas are included in this document: Sample transport including use of pneumatic tubes systems; clots in citrated samples; centrifugation; primary tube storage and stability; interfering substances including haemolysis, icterus and lipaemia; secondary aliquots—transport, storage and processing; preanalytical variables for platelet function testing. The following areas are excluded from this document, but are included in an associated ICSH document addressing collection of samples for coagulation tests in clinical laboratories; ordering tests; sample collection tube and anticoagulant; preparation of the patient; sample collection device; venous stasis before sample collection; order of draw when different sample types are collected; sample labelling; blood‐to‐anticoagulant ratio (tube filling); influence of haematocrit. The recommendations are based on published data in peer‐reviewed literature and expert opinion.